2017
DOI: 10.1090/tran/6831
|View full text |Cite
|
Sign up to set email alerts
|

A convergence to Brownian motion on sub-Riemannian manifolds

Abstract: This paper considers a classical question of approximation of Brownian motion by a random walk in the setting of a sub-Riemannian manifold M . To construct such a random walk we first address several issues related to the degeneracy of such a manifold. In particular, we define a family of sub-Laplacian operators naturally connected to the geometry of the underlining manifold. In the case when M is a Riemannian (non-degenerate) manifold, we recover the Laplace-Beltrami operator. We then construct the correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 21 publications
(20 reference statements)
0
25
0
Order By: Relevance
“…Another approach is to choose a k-dimensional linear subspace h q in T * q M transverse to the non compact directions of the cylinder (playing the role of the "most horizontal" geodesics) and to average on h q ∩ q . This last approach is essentially the one followed in [16,15,17,18]. Certainly the problem of finding a canonical subspace h q in T * q M is a non-trivial question and in general it is believed that it is not possible.…”
Section: The Sub-riemannian Microscopic Laplacianmentioning
confidence: 99%
“…Another approach is to choose a k-dimensional linear subspace h q in T * q M transverse to the non compact directions of the cylinder (playing the role of the "most horizontal" geodesics) and to average on h q ∩ q . This last approach is essentially the one followed in [16,15,17,18]. Certainly the problem of finding a canonical subspace h q in T * q M is a non-trivial question and in general it is believed that it is not possible.…”
Section: The Sub-riemannian Microscopic Laplacianmentioning
confidence: 99%
“…The operator L V has been introduced in [7], where it is shown that L V is the generator of a process which is the limit of a naturally constructed horizontal random walk. The operator L V can be viewed as the generator of a horizontal Brownian motion on M , the role played by the Laplace-Beltrami operator on Riemannian manifolds.…”
Section: The Operator L Vmentioning
confidence: 99%
“…Our approach is to compare two operators on a sub-Riemannian manifold M that can be thought of as geometrically canonical to the sub-Riemannian structure we have on M . One of these operators, L V , is a sub-Laplacian we constructed previously in [7]. The advantage of this construction is that while it is canonical with respect to the horizontal Brownian motion, we are able to define the sub-Laplacian without some a priori choice of measure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) A sub-Riemannian example is given by the Heisenberg group H, [10,27,38,41], realized as R 3 together with the non-commutative multiplication…”
Section: Finite Energy Coordinatesmentioning
confidence: 99%